What to do About Journalism? Journalism and the International academic world - Zelizer, Barbie (Brazilian journalism research, 2007)
I begin with a question that may seem to be labor the point to readers of this article but which I believe holds some of the key issues associated with contemporary journalism.“What to do about journalism?” is a question that has not only conceptual dimensions – as in what do we study when we think about journalism – but also pedagogic ones – how do we teach what we think we know – and, most importantly, pragmatic ones – what is journalism today? And how will we continue practicing it into the coming era? on this article I would like to think through some of the most important challenges facing the study of contemporary journalism. I’ll be drawing from my own work that has been somewhat focused on the fundamental question of what journalism is for.